Formulation and Antibacterial Activity Testing of Nanoemulsion Cream from Coriander Seed Extract (Coriandrum sativum L.) in Inhibiting Protein Synthesis of Staphylococcus aureus Bacteria - Intan Tasya Az Zahra; Dyah Mahendrasari Sukendra (Journal of Science and Technology Research for Pharmacy, 2025)
Bullous impetigo is a contagious skin infection caused by Staphylococcus aureus, characterized by the formation of fluid-filled bullae. The use of topical antibiotics for impetigo treatment has side effects, including the increased risk of bacterial resistance, leading to reduced efficacy. Natural alternatives such as coriander seeds (Coriandrum sativum L.) have the potential as antibacterial agents with fewer side effects. This study aimed to formulate and evaluate the antibacterial activity of a nanoemulsion cream containing coriander seed extract against Staphylococcus aureus. The extraction of coriander seeds was carried out using the maceration method with 96% ethanol to obtain a thick extract, followed by phytochemical screening to qualitatively identify bioactive compounds and a quantitative total flavonoid test, which resulted in a flavonoid content of 61.64 mg QE/g. The nanoemulsion was formulated using PEG 400 and VCO as the oil phase, while Tween 80, distilled water, and coriander seed extract at concentrations of 2.5%, 5%, and 7.5% were used as the aqueous phase. The nanoemulsion was then incorporated into a cream base containing stearic acid, cera alba, and white vaseline as the oil phase, and TEA, propylene glycol, methylparaben, and distilled water as the aqueous phase, heated in a water bath at 75°C. The resulting preparations were evaluated and tested for antibacterial activity using the well diffusion method. The bioactive compounds identified in coriander seed extract include alkaloids, saponins, tannins, terpenoids, and flavonoids, which exhibit antibacterial activity against Staphylococcus aureus. The antibacterial test results showed that the inhibition zones for F1 (2.5%), F2 (5%), and F3 (7.5%) were 15.00 mm, 22.00 mm, and 28.33 mm, respectively, while the positive control had an inhibition zone of 30.67 mm. The highest antibacterial activity was obtained at the F3 concentration (7.5%) with an inhibition zone diameter of 28.33 mm, classified as very strong.